Influence of siam weed compost on soybean varieties in an agroforestry system with kayu putih (Melaleuca cajuputi) - Priyono Suryanto; Eny Faridah; Handojo Hadi Nurjanto; SUPRIYANTA SUPRIYANTA; Dody Kastono; Eka Tarwaca Susila Putra; Suci Handayani; Anggraeni Kusuma Dewi; Taufan Alam (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Suryanto P, Faridah E, Nurjanto HH, Supriyanta, Kastono D, Putra ETS, Handayani S, Dewi AK, Alam T. 2020. Influence of siam weed compost on soybean varieties in an agroforestry system with kayu putih (Melaleuca cajuputi). Biodiversitas 21: 3062-3069. Siam weed (Chromolaena odorata (L.) R.M.King & H.Rob.) has grown wild in many kayu putih (Melaleuca cajuputi Powell) forest can be utilized as compost for complementary of inorganic fertilizers in annual crops. The experiment was conducted during November-February 2020 in Menggoran Forest Resort, Playen Forest Section, Yogyakarta Forest Management District, Indonesia. The experiment was arranged in a randomized complete block design (RCBD) with three replications. The first factor was soybean varieties consisted of Anjasmoro, Dering I, and Grobogan. The second factor was siam weed compost (SWC) application consisted of 0, 5, 10, and 15 tons ha-1. The data were analyzed using Two-way ANOVA, ANCOVA, and stepwise regression. The SWC application of 10 tons ha-1 showed the highest yield of Anjasmoro, Dering I, and Grobogan were 1.42, 1.56, and 1.51 tons ha-1, respectively, or increased by118.46%, 102.60%, and 112.68%, respectively, compared to the without SWC application. The optimum dosage of SWC application for Anjasmoro, Dering I, and Grobogan were 13.05, 14.35, and 14.93 tons ha-1, respectively, with a maximum yield of 1.45, 1.59, and 1.52 tons ha-1, respectively. Soil quality and physiological parameters that had a significant influenced on the production of soybean varieties in agroforestry systems with M. cajuputi were SOM, K, LPR, TC, and PRO.